Effects of COVID-19 on cognition and mood after hospitalization and at 2-month follow-up - Peskar, Manca; Šimunič, Boštjan; Šlosar, Luka; Pišot, Saša; Teraž, Kaja; Gasparini, Mladen; Pišot, Rado; Marusic, Uros (Frontiers in Psychology, 2023)
A plethora of evidence links SARS-CoV-2 infection with concomitant cognitive dysfunction, which often persists weeks to months after the acute stages of illness and affects executive function, attention, memory, orientation, and movement control. It remains largely unclear which conditions or factors exacerbate the recovery. In a cohort of N=37 Slovenian patients (5 females, aged M = 58, SD = 10.7 years) that were hospitalized because of COVID-19, the cognitive function and mood states were assessed immediately after discharge and 2-months later to investigate the early post-COVID recovery changes. We assessed the global Montreal Cognitive Assessment (MoCA), Simple and Choice Reaction Times, executive functions (Trail-Making Test – TMT-A and TMT-B), short-term memory (Auditory Verbal Learning Test – AVLT), and visuospatial memory. We monitored depressive and anxiety symptoms and applied general self-efficacy and cognitive complaints questionnaires. Our results showed a global cognitive impairment (MoCA, Z = 332.5; p = 0.012), poorer performance on executive functions (TMT-A, Z = 188; p = 0.014; and TMT-B, Z = 185; p = 0.012), verbal memory (AVLT, F = 33.4; p < 0.001), and delayed recall (AVLT7, F = 17.1; p < 0.001), and higher depressive (Z = 145; p = 0.015) and anxiety (Z = 141; p = 0.003) symptoms after hospital discharge compared to 2-month follow-up, indicating that SARS-CoV-2 may transiently impair cognitive function and adversely affect the mood. No improvement in MoCA was observed in 40.5% of the patients at follow-up, indicating possible long-term effects of COVID-19 on global cognitive performance. Medical comorbidities (p = 0.035) significantly predicted the change in MoCA score over time, while fat mass (FM, p = 0.518), Mediterranean diet index (p = .0.944), and Florida Cognitive Activities Score (p = 0.927) did not. These results suggest that the patients’ medical comorbidities at the time of SARS-CoV-2 infection could importantly contribute to the acute impairment of cognitive function and stress the importance of systemic implementation of countermeasures to limit the negative consequences on public health.